A. Barikko asarlarida an’anaviy dialogning transformasiyasi orqali postmodernizmining o‘ziga xos xususiyatlari - Rasulova , Munira (The Lingua Spectrum, 2025)
his article is devoted to the study of the transformation of traditional dialogue into postmodern dialogue in the works of the Italian writer Baricco. His creative activity develops in the historical and cultural context of the postmodern period, which can be seen in his works. This era is characterized by widespread information flows and the acceleration of globalization processes. The features of postmodern fiction that are considered canonical are intertextuality, metaliterature and genre mixing. A. Baricco fits into this context, questioning the great traditional narratives and emphasizing the importance of fragmentation and plurality of voices. His writing is characterized by the use of different styles reflecting the heterogeneity of modern reality. The stylistic dominant in Baricco‘s works is the transformation of traditional dialogue into a postmodern one: there is often a lack of author’s words in the dialogues of characters or in the chorus. There are also dialogues in which only one character’s lines are given, and the lines of the second are missing. Having analyzed the dialogues of some of the author’s works ("Ocean Sea", "Three Times at Dawn"), it was found that many of them lack the author’s words or lines of one of the characters. This factor provides the reader with the opportunity to freely interpret the potential content of the replicas due to the content-factual information available in the dialogues.